Opera in translation unity and diversity - Serban, Adriana; Chan, Kelly Kar Yue (Benjamins translation library ;, 2020)
"This volume covers aspects of opera translation within the Western world and in Asia, as well as some of opera's many travels between continents, countries, languages and cultures-and also between genres and media. The concept of 'adaptation' is a thread running through the sixteen contributions, which encompass a variety of composers, operas, periods and national traditions. Sung translation, libretto translation, surtitling, subtitling are discussed from a range of theoretical and methodological perspectives. Exploration of aspects such as the relationship between language and music, multimodality, intertextuality, cultural and linguistic transfer, multilingualism, humour, identity and stereotype, political ideology, the translator's voice and the role of the audience is driven by a shared motivation: a love of opera and of the beauty it has never ceased to provide through the centuries, and admiration for the people who write, compose, perform, direct, translate, or otherwise contribute to making the joy of opera a part of our lives"--